Kegawadaruratan Trauma Haemorrhage Antepartum di Wilayah Kerja Puskesmas Merdeka - Ningsih, Ratna; Rosnani, Rosnani; Jaya, Herawati (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2024)
Women's reproductive health must be prioritized because women experience the life cycle of pregnancy and childbirth. This cycle can cause complications, one of which is pregnancy, namely bleeding, the incidence of antepartum bleeding/haemorrhage/ HAP is very vulnerable when you are still pregnant (Trimester I) which is often associated with abortion. The impact of abortion is that it causes pain and even death for the mother. The aim of this community service activity consists of long-term goals that will be achieved including living, growing, reproducing and being able to carry out normal activities, while the short-term goal is that pregnant women can understand the prevention of incomplete abortion and how to handle it. The activity received enthusiastic health cadres, and support from the Head of the Merdeka Community Health Center, Head of the Nursing Department, Lecturers, and Students of the D3 Nursing Study Program in Palembang, Poltekkes, Ministry of Health, Palembang, with the result that almost all cadres experienced an increase in knowledge after attending trauma emergency training: antepartum haemorrhagia/ HAP/ pregnancy bleeding : incomplete abortion.